Restorative Justice as an Alternative Approach in Combating Corruption Offenses - Octaviyanti, Ary; Yanto, Oksidelfa (Journal of Legal and Cultural Analytics, 2024)
Corruption runs rampant in Indonesia, hindering progress, yet restorative justice promises a fair and sustainable solution to address this issue. This research aims to explore the application of restorative justice in tackling corruption in Indonesia. Utilizing a normative legal research method, the study highlights the challenges faced by restorative justice, such as difficulties in identifying victims and disagreements regarding restitution. The findings suggest that strengthening the norms of state restitution as the primary penalty and establishing recovery mechanisms are essential to bolster restorative justice. The conclusion drawn from this research is that implementing restorative justice in corruption cases allows victims to receive direct compensation from perpetrators, enhances accountability, and reduces the burden on the judicial system by resolving cases outside of court. This research is expected to serve as an effective instrument in combating corruption and rebuilding public trust in the justice system.